AN INTERVENTION PROGRAM TO IMPROVE NURSES’ COMPETENCIES IN DISASTER RESPONSE: A MIXED-METHODS STUDY PROTOCOL - Cut Husna; Hajjul Kamil; Mustanir Yahya; Teuku Tahlil (Belitung Nursing Journal, 2020)
Introduction: Indonesia has the highest risk and vulnerability to both natural and non-natural disasters in the world. Aceh Province located on the confluence of two earth fault plates has been discovered to be exposed to a higher risk leading to significant physical, emotional, and psychological problems. Therefore, there is a need for immediate disaster response efforts to reduce the impacts, and nurses are the largest care providers with adequate competencies to ensure effectiveness. Objective: The study aims to develop a study protocol to measure the effectiveness of the intervention program to improve nurses’ competencies in disaster response. Methods: A sequential exploratory mixed-method study design will be used. A qualitative phase is to explore nurses’ competencies in disaster response according to nurses, disaster survivors, hospitalized patients, members of the Ulama Consultative Assembly of Aceh, and hospital policymakers using FGDs and in-depth interviews. The result of this phase is to develop intervention and instruments. Data are analyzed using a content analysis. A quantitative phase is to examine the effectiveness of the initiated intervention programs on nurses’ competencies in disaster response with a randomized controlled trial study design. There will be three groups in this phase, namely Evidence-Based Intervention (EBI) group, Islamic-Based Intervention (IBI) group, and Control Group (CG). The nurses’ competencies related knowledge, skill, and attitude will be measured using valid and reliable instruments. Data will be analyzed using independent t-test, and a repeated measure one way ANOVA. Discussion: The findings are expected to be the basis for the development of appropriate tools and better intervention in nursing practice and education in relation to evidence and Islamic-based disaster curriculum as well as a guide for future research. Trial registration: on process with request number ANZCTR 378930